Mapping of mineral resources and lithological units: a review of remote sensing techniques. (3rd April 2019) - Rajan Girija, Rejith; Mayappan, Sundararajan
ABSTRACT: The remote sensing (RS) techniques have become a guiding and promising tool for mineral exploration and mapping of lithological units. The RS for mineral exploration begins with Landsat multispectral data in which the iron oxide and clay minerals associated with hydrothermal alteration zones were delineated using techniques like BR and PCA. Later, the advanced image processing techniques like spectral angle mapping, spectral feature fitting, Crosta technique and MNF transformation were successfully implemented to delineate clay, sulphate and iron oxide minerals using the shortwave infrared bands of Advanced Spaceborne Thermal Emission and Reflectance Radiometer (ASTER) data. The thermal bands of ASTER allowed mapping of carbonate and quartz mineralogy based on their silica content. The quantitative mapping of minerals started with the advent of hyperspectral RS data like Hyperion. The recent advances in satellite sensor technology get paralleled by the development of new and innovative approaches in RS data processing and integration. The studies have opened up new methods for mineral evaluation using sustainable and eco-friendly exploitation of natural resources. This paper provides a review of RS data products and techniques widely used for geological applications.